2014
DOI: 10.1001/jamapsychiatry.2013.4374
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plasma C-Reactive Protein as a Biomarker of Posttraumatic Stress Disorder Risk

Abstract: IMPORTANCE Posttraumatic stress disorder (PTSD) has been associated in cross-sectional studies with peripheral inflammation. It is not known whether this observed association is the result of PTSD predisposing to inflammation (as sometimes postulated) or to inflammation predisposing to PTSD.OBJECTIVE To determine whether plasma concentration of the inflammatory marker C-reactive protein (CRP) helps predict PTSD symptoms. DESIGN, SETTING, AND PARTICIPANTSThe Marine Resiliency Study, a prospective study of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 332 publications
(232 citation statements)
references
References 78 publications
14
203
1
4
Order By: Relevance
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 64%
See 1 more Smart Citation
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 64%
“…Of note, these associations were not simply explained by comorbid depression (Passos et al, 2015). In addition, genetic (Michopoulos et al, 2015) and longitudinal (Eraly et al, 2014) studies suggest that inflammation is a preexisting vulnerability factor for the development of PTSD in trauma-exposed individuals rather than simply a correlate of subjective distress, disease severity, or maladaptive coping strategies following PTSD onset.…”
Section: Observational Studies In Humansmentioning
confidence: 94%
“…Several studies (Green et al, 2016; Moon, Lee, Kim, & Hwang, 2013; Norte et al, 2013; Rissling et al, 2016; Wahbeh & Oken, 2013) found a decrease in HRV in patients with PTSD, pointing out that PTSD symptoms may be related to decreased parasympathetic control, especially during sleep (which could constitute a state of vulnerability for decreased parasympathetic cardiac control) (Kobayashi, Lavela, & Mellman, 2014). Other studies demonstrated that low HRV as a sign of over-reactivity to stress were present prior to the development of PTSD (Eraly et al, 2014; Minassian et al, 2015). …”
Section: Resultsmentioning
confidence: 95%
“…Studies have been conducted and are underway using both adrenergic antagonists and synthetic glucocorticoids in the context of acute trauma to prevent development of PTSD (Amos et al, 2014). Nevertheless, although increased inflammatory markers including CRP have been shown to predict the subsequent development of PTSD (Eraly et al, 2014;Michopoulos et al, 2015), no studies have determined whether those individuals with increased inflammatory markers are the ones who might be most likely to respond to adrenergic or glucocorticoid agonists. Moreover, whether the success of these interventions is in part due to inhibition of stress-induced inflammatory responses or even through glucocorticoid-mediated trafficking of neuroprotective T cells to the brain has yet to be established.…”
Section: Reviewmentioning
confidence: 99%